Electron-beam-induced formation of Zn nanocrystal islands in a SiO2 layer - Kim, Tae Whan; Shin, Jae Won; Lee, Jeong Yong; Jung, Jae Hun; Lee, Jung Wook; Choi, Won Kook; Jin, Sungho (AMER INST PHYSICS, 2007)
Electron-beam-induced Zn nanocrystal islands were formed in a dielectric SiO2 layer. When a ZnO thin film on a p-type Si with amorphous SiOx interface layer is subjected to a 900 degrees C annealing followed by electron irradiation in a transmission electron microscope environment, an amorphous Zn2xSi1-xO2 layer is formed. Upon irradiation with a 300 keV electrons, metallic and single crystal nanoislands of Zn with similar to 7-10 nm diameter were formed and embedded within the SiO2 interface layer. Possible mechanisms for the formation of Zn nanocrystals are presented.
Keywords: QUANTUM-DOT; SILICON NANOCRYSTALS; ROOM-TEMPERATURE; COULOMB-BLOCKADE; FABRICATION; TRANSISTORS; MICROSCOPE; SYSTEM; MEMORY; FIELD